Use of botulinum toxin in Frey's syndrome - Francesco Freni; Francesco Gazia; Ferdinando Stagno d’Alcontres; Bruno Galletti; Francesco Galletti (Clinical Case Reports, 2019)
Key Clinical Message Frey's syndrome is the most common adverse event after parotidectomy, and usually, it appears after 6 months. In our case, symptoms appear 20 years from surgery, an uncommon condition. Intralesional botulinum toxin gives excellent results in therapy, regardless of the time elapsed between surgery and the first treatment.